2006
DOI: 10.1590/s1517-83822006000300008
|View full text |Cite
|
Sign up to set email alerts
|

Candida dubliniensis in a Brazilian family with an HIV 1- infected child: identification, antifungal susceptibility, drug accumulation and sterol composition

Abstract: This study investigated the prevalence of C. dubliniensis in a Brazilian family with an HIV -infected child. A total of 42 oral isolates were obtained from eight family members. The identification of C. dubliniensis was performed by polymerase chain reactions (PCR) using primers against a specific sequence of the C. dubliniensis cytochrome b gene. Only the HIV-infected child and his grandmother were colonized by C. dubliniensis. In this study C. dubliniensis isolated from the HIV-infected child exhibited high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…C. dubliniensis has been frequently associated to oral and systemic candidiasis in HIV-positive patients 4,19,23 under chemotherapy and bone marrow transplant patients 3,18 , sometimes liable for death cases 28 . Thus, it is very important to identify among the population of immunossuppressed patients those who have C. dubliniensis in their oral microbiota, and how big is this ratio (cfu/mL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. dubliniensis has been frequently associated to oral and systemic candidiasis in HIV-positive patients 4,19,23 under chemotherapy and bone marrow transplant patients 3,18 , sometimes liable for death cases 28 . Thus, it is very important to identify among the population of immunossuppressed patients those who have C. dubliniensis in their oral microbiota, and how big is this ratio (cfu/mL).…”
Section: Discussionmentioning
confidence: 99%
“…C. dubliniensis has many phenotypic features with C. albicans and the incidence of candidemia due C. dubliniensis is unknown mainly because of difficulty in distinguishing these two strains 11 , 17 , 27 . C. dubliniensis has been frequently associated to oral and systemic candidiasis in HIV-positive patients 4 , 19 , 23 under chemotherapy and bone marrow transplant patients 3 , 18 , sometimes liable for death cases 28 . Thus, it is very important to identify among the population of immunossuppressed patients those who have C. dubliniensis in their oral microbiota, and how big is this ratio (cfu/mL).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these, there is C. dubliniensis, a more recently described species. It has been reported that this species has a virulence similar to that of C. albicans , due to their genomic similarity (36), and it is frequently isolated in HIV-positive patients (25). …”
Section: Introductionmentioning
confidence: 99%